eCM 2017
DOI: 10.22203/ecm.v034a03
|View full text |Cite
|
Sign up to set email alerts
|

The role of laminins in cartilaginous tissues: from development to regeneration

Abstract: As a key molecule of extracellular matrix, laminin provides a delicate microenvironment for cell functions. Recent findings suggest that laminins expressed by cartilage-forming cells (chondrocytes, progenitor cells and stem cells) could promote chondrogenesis. However, few papers outline the effect of laminins on providing a favorable matrix microenvironment for cartilage regeneration. In this review, we delineated the expression of laminins in hyaline cartilage, fibrocartilage and cartilage-like tissue (nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 106 publications
1
23
0
1
Order By: Relevance
“…Nevertheless, laminins mainly dictate the structure and assembly of MB [77]. Moreover, these glycoproteins play a crucial role in cell migration, adhesion, differentiation, and wound healing [78][79][80][81]. They also participate in early embryonic development and organogenesis.…”
Section: Lamininsmentioning
confidence: 99%
“…Nevertheless, laminins mainly dictate the structure and assembly of MB [77]. Moreover, these glycoproteins play a crucial role in cell migration, adhesion, differentiation, and wound healing [78][79][80][81]. They also participate in early embryonic development and organogenesis.…”
Section: Lamininsmentioning
confidence: 99%
“…Laminins are a family of heterotrimeric ECM proteins 33 . Previous studies have shown the expressions of specific laminins were differentially regulated during development, adhesion, migration and regeneration [34][35][36] . In our study, LAMA2 was observed to be up-regulated in KBD group in comparison to OA.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, NID2 and COL4A5 were significantly more highly expressed in ScASCs compared to donor-matched IPFSCs. Given the function of HSPG2 encoding perlecan as the "factotum" in cartilage (Melrose et al, 2008) and the role of laminins in cartilage regeneration (Sun et al, 2017), NID2 and COL4A5 expression might be associated with adipogenic differentiation, which remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%